Pleural Effusion in Pulmonary Tuberculosis Patients: A Case Review and Diagnostic Challenges with Radiological Examination - Nidaul Khairy Nurfan; Shofiyah Latief; Nur Ahmad Tabri (The International Journal of Medical Science and Health Research, 2025)
Tuberculous pleural effusion is a common form of extrapulmonary tuberculosis, especially in regions with a high tuberculosis incidence. This condition may result from an immunological response to Mycobacterium tuberculosis infection or the rupture of subpleural lesions into the pleural cavity. This study aims to assess the role of radiological examination in diagnosing tuberculous pleural effusion and compare the accuracy of different imaging modalities, including chest radiography, computed tomography (CT) scans, and ultrasonography. The study adopts an analytical observational design involving a 74-year-old male patient suspected of having pulmonary tuberculosis with right-sided pleural effusion. The diagnosis was supported by clinical evaluation, radiological assessment, and laboratory analysis of pleural fluid. Chest radiography in the posteroanterior (PA) position revealed active pulmonary tuberculosis with right pleural effusion. Radiological examinations, particularly CT scans and ultrasonography, play a crucial role in distinguishing tuberculous pleural effusion from other causes, such as malignancy or parapneumonic effusion. Early detection through accurate imaging facilitates better clinical decision-making, ensuring optimal patient treatment.